ECG Noise Removal Using FCN DAE Method - Kollem, Sreedhar; Baig, Mirza Rahman; Lasya, Donthireddy; Kalyan, Eligeti Ashwad; Varma, Karre Nithin (2022 2nd International Conference on Intelligent Technologies (CONIT), 2022)
An electrocardiogram (ECG) is a straightforward test that measures your heart rate and electrical activity. Electrical signals produced by your heart are detected by skin-connected nerves each time it beats. ECG signals are susceptible to noise contamination in real-world conditions, which can lead to misunderstanding. Baseline wanders and power line interference are the two main sources of noise in the ECG signal. To tackle these problems and eliminate inaccuracies, special emphasis has been dedicated to interpreting the ECG in order to achieve a precise diagnosis and analysis. To recycle pure data in its audio version, a denoising autoencoder (DAE) might be utilized. The results of experiments on ECG signals with various degrees of SNR input reveal that FCN outperforms fully connected neural network-and convolutional neural-based denoising network models significantly.